South African writings of Morris Hoffman : between Yiddish and Hebrew - Ḳoṭlerman, Ber Boris (Journal for semitics, 2014)
Morris Hoffman (1885-1940), who was born in a Latvian township and emigrated to South Africa in 1906, was a brilliant example of the Eastern European Jewish maskil writing with equal fluency in both Yiddish and Hebrew. He published poetry and prose in South African Yiddish and Hebrew periodicals. His long Yiddish poem under the title Afrikaner epopeyen (African epics) was considered to be the best Yiddish poetry written in South Africa. In 1939, a selection of his Yiddish stories under the title Unter afrikaner zun (Under the African sun) was prepared for publishing in De Aar, Cape Province (which is now in the Northern Cape Province), and published after his death in 1951 in Johannesburg. The Hebrew version of the stories was published in Israel in 1949 under the title Tahat shmey afrikah (Under the skies of Africa). The article deals with certain differences between the versions using the example of one of the bilingual stories. The comparison between the versions illuminates Hoffman's reflections on the relations between Jews and Afrikaners with a rather new perspective which underlines their religious background.